The Factors Affecting Post Date Pregnancy in Third Trimester Pregnant Women at Balung Regional Hospital Jember District in 2019 - Jenie Palupi; Yuniasih; Purwaningrum; Siska Atik Maryanti; Bethari Anindito A (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Introduction: An overdue pregnancy or post date pregnancy is one that lasts between 40 and 42 weeks. Late pregnancy can be caused by several factors, including age, gravida, fetal location, and post date history. Objective: The purpose of this study was to identify and analyze the Factors Affecting Post Date Pregnancy at Balung Regional hospital in 2019. Post date can increase the risk of perinatal mortality and morbidity Methods: The design in this study is a descriptive analytic method with a cross sectional approach, using simple random sampling consisting of 620 pregnant women in the third trimester. Data were analyzed by chi-square test. The results of this study were 53.5% of pregnant women in the third trimester aged 20-34 years, 52.49% of multigravida mothers, 74.5% of mothers with normal fetal position and 73.7% of mothers without post-date history.). Results: The results of bivariate analysis showed that the age factor indicated (p = 0.000), gravida (p = 0.000), fetal location (p = 0.000), post date history (p = 0.000). Significance value showed 0.000 < 0.050. Thus (X2 Count > X2 table) it is concluded that H0 is rejected. Conclusion: It is hoped that the results of community research are more selective in planning pregnancy programs and increasing the role of families in actively participating in the welfare of pregnant women and fetuses.